PELAKSANAAN TUGAS BELLBOY PADA FRONT OFFICE DEPARTMENT DI FOX HOTEL PEKANBARU - Pro Sutejo Pasaribu; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Execution of tasks is a way or steps so that the implementation of work is easy and smooth. In a hotel it is very important to pay attention to the procedure for carrying out the bellboy duties that will be carried out. This study aims to find out how important the attention of hotel management is in carrying out bellboy duties, handling guest goods, recording guest luggage, recording temporary guest safekeeping, sending guest messages and what obstacles are experienced by bellboys when carrying out their duties taken from book sources Agustinus Darsono (2001) in the front office bellboy section of the Fox Hotel Pekanbaru department. Data collected using interview techniques, observation and documentation. Based on the research obtained from the results of the interviews that the implementation of the bellboy duties at the front office department of the Fox Hotel Pekanbaru can be said to be quite good because some have followed the procedures and some are still not in accordance with the procedures that have been determined. Keywords: Implementation, Bellboy, Front Office Department, Fox Hotel Pekanbaru.